2021
DOI: 10.3389/fagro.2021.689972
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Microbe Mediated Uptake of Essential Nutrients (Fe, P, K) for Crop Stress Management: Microbe–Soil–Plant Continuum

Abstract: The indiscriminate and intensive use of agrochemicals in developing nations to enhance crop productivity has posed an alarming threat to soil quality, fertility, biodiversity, food safety, agricultural sustainability, and groundwater quality, thus critically affecting planetary health and food productivity. Additionally, both abiotic and biotic stresses and developmental disorders, i.e., disease susceptibility, hormonal imbalance, and nutritional deficiency, are the major constraints on crop productivity. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 132 publications
1
7
0
Order By: Relevance
“…In addition, it has been observed that MP1 treatment altered the microbial diversity with an increment in Firmicutes percentage over uninoculated control at both locations. Previous studies have positively correlated the proteobacterial and firmicute abundance with higher nutrient mobilization and improved soil fertility (Pattnaik et al, 2021;Suyal et al, 2021a). Further, in accordance with the present study, cold adaptive Cyanobacteria, Acidobacteria, Planctomycetes, Gemmatimonadetes, Firmicutes, and Nitrospirae phylum were also reported from higher altitude agroecosystems (Suyal et al, 2015;Suyal et al, 2021b).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it has been observed that MP1 treatment altered the microbial diversity with an increment in Firmicutes percentage over uninoculated control at both locations. Previous studies have positively correlated the proteobacterial and firmicute abundance with higher nutrient mobilization and improved soil fertility (Pattnaik et al, 2021;Suyal et al, 2021a). Further, in accordance with the present study, cold adaptive Cyanobacteria, Acidobacteria, Planctomycetes, Gemmatimonadetes, Firmicutes, and Nitrospirae phylum were also reported from higher altitude agroecosystems (Suyal et al, 2015;Suyal et al, 2021b).…”
Section: Discussionsupporting
confidence: 92%
“…Some of them are responsible for the acquisition of minerals and nutrients from soil solutes, while others play important role in the transport of minerals from root hairs to sieve tubes and xylem bundles and subsequent transport to shoots. In plants, some of the key phosphate transporters are phosphate transporter PHO1 homolog 3, phosphate transporter PHO, inorganic phosphate transporters 1-4, probable inorganic phosphate transporters 1-3, and phosphate transporter PHO1 homolog 9 (Kulcheski et al, 2015;Suleman et al, 2018;Pattnaik et al, 2021). Several reports indicated the role of potassium transporters in the acquisition and transport of potassium from soil to plant roots and then shoot.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated the role of potassium transporters in the acquisition and transport of potassium from soil to plant roots and then shoot. However, potassium can be easily acquired by roots via Na + /K + flux and other ion channels (Kulcheski et al, 2015;Pattnaik et al, 2021). Similarly, in the recent past, a number of sulfate transporters were identified in a large number of plant species.…”
Section: Discussionmentioning
confidence: 99%
“…23 Ion (Fe) plays a crucial role in cell metabolism, encompassing vital processes such as chlorophyll synthesis, maintenance of chloroplast function, respiration, DNA synthesis, and severing as a prosthetic group for numerous metallo-enzymes involved in redox reactions. 24 Previous studies have indicated that foliar application with the Fe 2 O 3 NMs (30 mg L −1 ) significantly increased the nodule and shoot biomass of soybeans by 99.0 and 55.4%, respectively. These improvements were found to be 2.6- and 2.0-fold higher compared to the use of commercially available iron fertilizers containing equivalent amounts of Fe.…”
Section: Introductionmentioning
confidence: 93%